2014
DOI: 10.1177/0961203313517405
|View full text |Cite
|
Sign up to set email alerts
|

Circulating FABP4 is a marker of metabolic and cardiovascular risk in SLE patients

Abstract: The aim of this study is to determine if circulating fatty acid-binding protein 4 (FABP4) plasma levels are a possible marker of metabolic risk in SLE patients. Circulating levels of adipose FABP4 are associated with adiposity, insulin resistance (IR), metabolic syndrome, diabetes and cardiovascular diseases. Patients affected by systemic lupus erythematosus (SLE) show an accelerated atherosclerosis that cannot be entirely explained by traditional cardiovascular risk factors. Sixty consecutive patients with SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
(64 reference statements)
0
19
1
1
Order By: Relevance
“…After reading titles or abstracts, 1846 records were removed because of duplication, irrelevance to SLE or our topic or review. Finally, 47 eligible studies which met the inclusion criteria were identified and included in this meta‐analysis . The detailed selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading titles or abstracts, 1846 records were removed because of duplication, irrelevance to SLE or our topic or review. Finally, 47 eligible studies which met the inclusion criteria were identified and included in this meta‐analysis . The detailed selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic criteria of MetS met those of the National Cholesterol Education Program Adult Treatment Panel III (NCEP/ATPIII), World health Organization (WHO), the American Heart Association/National Heart, Lung, and Blood Institute Scientific Statement (AHA/NHLBI),, the International Diabetes Federation (IDF), the European Group for the study of Insulin‐Resistance (EGIR) and the Chinese Diabetes Society (CDS). In five studies, MetS was diagnosed with NCEP‐ATPIII and WHO or EGIR and WHO, and the data of NCEP‐ATPIII or EGIR were used for pooled meta‐analysis . Of all the included articles, 24 articles had control groups which were used to explore the relationship of SLE and the risks of MetS …”
Section: Resultsmentioning
confidence: 99%
“…Our group has focused on research regarding surrogate markers of subclinical atherosclerosis in SLE patients and a more detailed method to analyze the lipid profile by nuclear magnetic resonance (NMR), because standard laboratory methods did not reflect the real atherogenic lipid profile in these patients (27)(28)(29). We have also observed that some specific SLE-related factors, such as complement system factors and antiphospholipid antibodies (aPL), are also associated with carotid IMT thickness and some lipoproteins measured by NMR, such as intermediatedensity lipoprotein (IDL) particles and small dense high-density lipoprotein (HDL) particles (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid binding protein 4 (FABP4), a cytoplasmic fatty acid chaperone, is expressed in both adipocytes and macrophages [9]. It plays a vital role in the metabolic dysfunction that underlies the relationship between inflammatory events and lipid metabolism [10]. High FABP4 levels in atherosclerotic lesions are associated with an unstable plaque phenotype and increased risk of cardiovascular events [11].…”
Section: Introductionmentioning
confidence: 99%